Evaluating Value-Based Vocational Education Using Logic Model: A Qualitative Inquiry in Islamic Higher Education - Aziz, Muh. Bachtiar; Amir, Ahmad Nabil (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study fills a critical gap in understanding how Islamic values are meaningfully integrated into vocational education programs across Indonesia's Islamic higher education institutions. It investigates the integration of Islamic values into the vocational training program at the Faculty of Tarbiyah, IAIN Bone, and hypothesizes that such integration significantly contributes to students' character development. Using a qualitative approach based on a logic model mini-assessment, the research involved interviews, observations, and document analysis to evaluate the program's inputs, activities, outputs, outcomes, and impacts. The findings reveal that Islamic values are embedded not only through formal curriculum but also through informal mentoring, a religiously supportive environment, and reflective practices. These results highlight that strong foundational inputs and intentional soft skills development, reinforced by educators’ role modeling, effectively shape students' character and offer a replicable framework for value-based vocational education.